THE CONCEPT OF INTEGRATING INFOCOMMUNICATION TECHNOLOGY FOR ENCODING VIDEO SEGMENTS INTO STANDARDIZED PLATFORMS. - Barannik, Vladimir; Shulgin, Sergii; Onyshchenko, Roman; Babenko, Mykhailo; Elіseev, Evgenіy (Science-based technologies, 2024)
The article proves the necessity of creation and development of domestic infocommunication coding technologies. This is due to the presence in the process of using existing technologies for encoding video information resources of the problems It is associated with the emergence of an imbalance between: the constantly increasing level of intensity of the bit description of information flows and the limited performance characteristics of telecommunication technologies, which can be used in crisis conditions. An approach to resolving imbalances is proved. This is possible through the use of more efficient video encoding technologies. Such technologies make it possible to reduce the bit volume of video information streams. However, as shown in the article, existing concepts are characterized by systemic shortcomings. They are due to the presence of an imbalance. On the one hand, the main factor in reducing the bit volume of video data is determined by the amount of psychovisual (PSV) redundancy. On the other hand, the amount of such redundancy is limited for video images in certain applications. The article proposes to improve the technologies of video image encoding according to the segment-oriented concept on the basis of additional establishment and reduction of the number of structural redundancy. It is argued that the relevant direction concerns the development and use of truncated-positional coding technologies in the process of reducing the redundancy of transformed video segments. However, this concept refers to the processing of individual video segments. The question arises of the need to integrate it into standardized platforms. The possibility of integration of the created technology at the level of encoding of video segments of the standardized process of video frame processing is substantiated. This is ensured by the availability of the capacity to: ensure interoperability between the created video segment encoding technology and the standardized video frame processing platform; possibilities for constructing a technology for encoding sets of auxiliary components of truncated-positional space. This creates conditions for parametric compatibility between specific sets of service information of each technological concept.